Prevalence and related factors of depression among healthcare personnel at primary healthcare centers - Eusof Izzudin, Md Parvez; Al-Bedri, Ayman; Subramaniam, Vengadesh; Matthews @ Machap, Puspamary; Cheong, Ai Theng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Depressive disorders are common. As compared to the general population, healthcare personnel are hypothesized to have an above than average risk to develop this condition. The aim of this study is to assess the prevalence of this condition and its contributing factors amongst primary healthcare personnel. Methods: A cross-sectional study was conducted by universally sampling 179 primary healthcare personnel at nine primary healthcare centers across Kuala Lumpur and Selangor in May 2015. Depressive symptoms were screened using self-administered Patient Health Questionnaire-9 (PHQ-9) questionnaire. Socio-demographic and work profile data were also assessed. Results: 92.7% of the 179 personnel agreed to participate. Near half of the respondents were staff nurses (49%), followed by doctors (22%), assistant medical officers (10%), attendants (10%) and the remaining were pharmacists, dieticians, and laboratory technicians (9%). Depression was found to be present in 38% of the participants with one-third found to have moderate to severe depression. Bivariate analysis show that males (p=0.043), assistant medical officers (p=0.048), and working more than 10 hours per day (p=0.019) are significant risk factors. Further analysis by logistic regression shows that working more than 10 hours per day increases the odds of depression by 3.1 (OR 3.1, 95% CI 1.1-8.7, p=0.03). Conclusions: A high prevalence of depression was found within the healthcare personnel population at the primary healthcare centres studied. Being a male, employed as an assistant medical officer, and, prolonged hours at the workplace is a significant risk factor for depression.